A non-fullerene electron acceptor with a spirobifluorene core and four diketopyrrolopyrrole arms end capped by 4-fluorobenzene. (August 2017) - Yuan, Cuixia; Liu, Wenqing; Shi, Minmin; Li, Shuixing; Wang, Yuzhou; Chen, Huanle; Li, Chang-Zhi; Chen, Hongzheng
Abstract: In this paper, a non-fullerene electron acceptor, SF(DPPFB)4, which owns a spirobifluorene core and four diketopyrrolopyrrole (DPP) arms end capped by 4-fluorobenzene, is designed and synthesized for solution-processable organic solar cells (OSCs). SF(DPPFB)4 shows similar absorption bands as those of its non-fluorinated parent compound, SF(DPPB)4 . However, the terminal fluorine atoms reduce the energy levels of SF(DPPFB)4, especially, its lowest unoccupied molecular orbital level decreases by 0.04 eV than that of SF(DPPB)4, which enlarges the energy offset between the electron donor and acceptor, favorable for the dissociation of excitons in OSCs. Moreover, the fluorination improves the electron mobility of SF(DPPFB)4 . Thus, the OSCs with poly(3-hexylthiophene) as the electron donor and SF(DPPFB)4 as the electron acceptor can provide a maximum power conversion efficiency of 4.42%, with a lifted short-circuit current ( J sc ) of 8.48 mA cm −2 . Highlights: A non-fullerene electron acceptor, SF(DPPFB)4, is designed and synthesized. SF(DPPFB)4 has four fluorine atoms as the terminal groups. The introduction of fluorine atoms decreases the energy levels of SF(DPPFB)4 . The fluorination also enhances the electron mobility of SF(DPPFB)4 . The OSCs with SF(DPPFB)4 as the electron acceptor show the improved currents.